Perancangan Semigantry Crane Kapasitas 60 Ton - , RIZAL BANU AJI; , Ir. Andr. Surjaka Isp., MT. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Semigantry crane is a machine or device which used to move commodity loaded weight is suspended or maximum load capacity of the machine, goods, and moving from one place to another within a certain distance. Semigantry crane is also one of the treatment machine tools continue to be developed to date. Development was based on the use of pulley and wheel using an electric motor. The expansion is to use an electric motor designed so that users are not too many devices relying so not too tired in work and reduce the time wasted when operating tools. Considerations made in analyzing the crane's ability to withstand a certain load is the type of material used to make the frame semigantry cranes, heavy calculate the maximum load that can be lifted semigantry crane, calculate the tensile pull (tensile stress), shear stress (shear stress), and tensile bend (bending stress). Type of material selected to make semigantry frame crane is ASTM A36 which is a standard steel alloy which is commonly used structural steel in the United States. A36 is Low carbon steel standard, without advanced alloys. As with most steels,A36 has a density 7.800 kg/m3 (0.28 lb / cu in). Young's modulus (elasticity) for A36 steel is 200 GPa (29 million psi). A36 has a Poisson ratio of steel count .260, and shear modulus of 79.3 GPa (11,500,000 psi). Basically a design tool can be said to be perfect when the tool design have quality, quantity and price realization affordable